Influence Of Price, Location And Quality Of Service Towards Customer Loyalty Mediated By Satisfaction (Study On Consumers Of Lamongan Boran Rice) - Safiratun Najah; Sabilar Rosyad; Indira Shofia Maulida (Sean Institute, 2024)
The development of the culinary industry is increasing, initially only as consumption, now it is a lifestyle. Culinary in Lamongan City has a role in economic growth in Indonesia, namely Nasi Boran. This study aims to analyze the factors that influence the loyalty of Nasi Boran customers in Lamongan. This study uses quantitative research and data obtained from questionnaires filled out by respondents. The population used includes all consumers who have consumed Nasi Boran Mbak Ita Lamongan and the sample used based on Hair's formula was 160 respondents. Data analysis using PLS-SEM. The results showed that price, location and service quality had no effect on customer loyalty. Price and service quality have no effect on customer satisfaction. Location has an effect on customer satisfaction. Customer satisfaction has no effect on customer loyalty. Price and service quality have no effect on customer loyalty mediated by satisfaction. Location affects customer loyalty mediated by satisfaction.